Leadership in the Innovation Era: Transactional or Transformational Style? - Putra, Arman Syah; Waruwu, Hatoli; Asbari, Masduki; Novitasari, Dewiana; Purwanto, Agus (International Journal of Social and Management Studies, 2020)
The purpose of this study was to measure and compare the influence of transactional and transformational leadership on lecturer innovation capability. Data were collected by using simple random sampling to the lecturer population of private higher education in Indonesia. The number of returned and valid questionnaires was 101 samples. Data were processed by using SEM with SmartPLS 3.0. The results of the study concluded that transactional and transformational leadership had a positive and significant influence on lecturer innovation capability. This study proposed a model for improving the lecturer innovation capability of lecturers in Indonesia through enhancing leadership practice in higher education organizations. This study can open the way to improve lecturer readiness in facing the education 4.0 era.